Cognitive Functions and Cognitive Reserve in Relation to Blood Pressure Components in a Population-Based Cohort Aged 53 to 94 Years. (4th April 2012) - Giordano, Nunzia; Tikhonoff, Valérie; Palatini, Paolo; Bascelli, Anna; Boschetti, Giovanni; De Lazzari, Fabia; Grasselli, Carla; Martini, Bortolo; Caffi, Sandro; Piccoli, Antonio; Mazza, Alberto; Bisiacchi, Patrizia; et al.
Abstract : In 288 men and women from general population in a cross-sectional survey, all neuropsychological tests were negatively associated with age; memory and executive function were also positively related with education. The hypertensives (HT) were less efficient than the normotensives (NT) in the test of memory with interference at 10 sec (MI-10) (−33%, P = 0.03 ), clock drawing test (CLOX) (−28%, P < 0.01 ), and mini-mental state examination (MMSE) (−6%, P = 0.02 ). Lower MMSE, MI-10, and CLOX were predicted by higher systolic (odds ratio, OR, 0.97, P = 0.02 ; OR 0.98, P < 0.005 ; OR 0.95, P < 0.001 ) and higher pulse blood pressure (BP) (OR 0.97, P = 0.02 ; OR 0.97, P < 0.01 ; and 0.95, P < 0.0001 ). The cognitive reserve index (CRI) was 6% lower in the HT (P = 0.03 ) and was predicted by higher pulse BP (OR 0.82, P < 0.001 ). The BP vectors of lower MMSE, MI-10, and CLOX were directed towards higher values of systolic and diastolic BP, that of low CRI towards higher systolic and lower diastolic. The label of hypertension and higher values of systolic or pulse BP are associated to worse memory and executive functions. Higher diastolic BP, although insufficient to impair cognition, strengthens this association. CRI is predicted by higher systolic BP associated to lower diastolic BP.